0682 Cognitive-behavioral therapy for insomnia alleviates and prevents suicidal ideation. (25th May 2022) - Kalmbach, David; Cheng, Philip; Reffi, Anthony; Ahmedani, Brian; Peterson, Edward; Seymour, Grace; Sagong, Chaewon; Sultan, Zain; Drak, Christopher
Abstract: Introduction: Patients with insomnia disorder are at increased risk for suicidal thoughts and behaviors. Early evidence suggests that insomnia therapeutics may reduce suicidal ideation (SI). However, the role of digital insomnia therapeutics in both the alleviation and prevention of SI remains unclear. Methods: A total of 658 community adults with DSM-5 insomnia disorder enrolled into a single-site RCT evaluating the efficacy of digital cognitive behavioral therapy for insomnia (CBTI) relative to attention control. Before treatment, 126 patients endorsed SI, whereas 532 patients denied SI. First, we tested whether CBTI can reduce SI in patients with baseline SI. Second, we tested whether CBTI reduces risk for SI development in those without baseline SI. Results: Among those with baseline SI, just 30.0% of CBTI patients reported SI after treatment, which was lower than the 54.5% of controls with posttreatment SI (OR=2.81, p=.006). Among those without baseline SI, CBTI did not reduce risk for developing SI after treatment (p=.681). However, a multivariate logit model regression odds for SI onto condition (p=.140) and posttreatment remission status (OR=5.68, p=.007) indicated that patients who remitted from insomnia exhibited a reduction in SI risk. Importantly, CBTI was associated with a 6.29 odds increase of insomnia remission relative to control. PRODCLIN estimation of the indirect effect indicated that CBTI prevents SI, but that the effect is fully mediated by the extent to which CBTI produces insomnia remission (αβ=-3.13=5, 95% CI=-5.28, -0.96). Conclusion: Digital CBTI reduces risk for SI development in insomnia patients without pretreatment SI. These data support a role for digital insomnia therapeutics in SI prevention in this high-risk patient population. Moreover, digital CBTI reduces SI in insomnia patients with SI. These data indicate that digital CBTI can alleviate SI, but it possible that adjunct treatment directly targeting SI may enhance suicide risk reduction. Support (If Any): Robert Wood Johnson Foundation